DEVELOPMENT OF RECIPE AND TECHNOLOGY OF COMBINEDSEMI-FINISHED PRODUCTS - L. . Kaimbayeva; A. . Tayeva; T. . Kulmagambetov; D. . Tapalova; M. . Fesenko; E. . Pereneseeva (Алматы технологиялық университетінің хабаршысы, 2021)
The authors set the goal - to develop a formulation of semi-finished meat and vegetable horse meat, poultry, minced eggplant. Compiled by experienced formulation of model samples of meat and vegetable raw materials. In model samples of minced meat the pH was studied, organoleptic characteristics and output were determined in the finished experimental products. As a result of experimental studies, the recipe of meat and cereal cutlets with the optimal ratio of raw materials has been established.